Halogen Bond-Driven Oxa-Pictet–Spengler Cyclization Using CBr₄: A Metal-Free and Regioselective Approach for the Synthesis of Tetracyclic Dihydrochromenoindole Scaffolds - Bansal, Diksha; Sivaganesan, Pooja; Sivaprasad, Ghanashyam; Ilango, Janani; Das, Mrinal K.; Chaudhuri, Saikat (Synlett, 2025)
Halogenated organic compounds have long served as valuable reagents in synthetic chemistry due to their distinctive reactivity and catalytic profiles. Among them, carbon tetrabromide (CBr₄) has recently gained attention as an efficient, metal-free catalyst capable of promoting selective bond activation under mild conditions. In this study, we exploit the catalytic utility of CBr₄ to develop an operationally simple and regioselective synthesis of dihydrochromenoindole-fused heterocyclic frameworks; the scaffolds known for their diverse biological activities, including anti-inflammatory, anticancer, and antimicrobial properties. Compared to existing protocols that often require transition-metal catalysts, pre-functionalized substrates, or harsh conditions, the present method offers a sustainable alternative with high yields and broad substrate compatibility. All synthesized compounds were fully characterized using 1H NMR, 13C NMR, DEPT-35, and mass spectrometry. Furthermore, a successful scale-up synthesis underscores the practicality and robustness of this protocol. This methodology not only improves access to bioactive dihydrochromenoindoles but also highlights the potential of CBr₄ as a green and cost-effective catalyst in heterocyclic synthesis.
Keywords: Tetracyclic dihydrochromeno indoles; Carbon tetrabromide; Heterocyclic synthesis; Metal-free catalysis; Regioselective annulation